Twitter and the 2022 Brazilian Elections Portrait: A Network and Content-Driven Analysis - Malagoli, Larissa; Piorino, Giovana; Ferreira, Carlos H. G.; Silva, Ana Paula Couto da (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2024)
The influence of online social networks on people’s actions and beliefs has grown significantly over the past decade, impacting everyday life. This is especially evident in Brazil, where these platforms have been instrumental in disseminating political content rapidly and widely. In this work, we aim to understand how the political debate surrounding the Brazilian elections of 2022 on Twitter unfolds through different levels of user engagement. We provide a content analysis that unveils the main topics discussed by different users, regardless of the strength of their interactions. Our results enrich the understanding of how online discussions evolved on social media during this important event in the recent history of democracy in Brazil.